Monitoring mood state to improve performance in soccer players: A brief review - Selmi, Okba; Ouergui, Ibrahim; Muscella, Antonella; Levitt, Danielle E.; Suzuki, Katsuhiko; Bouassida, Anissa (Frontiers in Psychology, 2023)
Introduction Psychological aspects of sport are key in maintaining athlete motivation and make a difference in competitive outcomes. Adjustments to training may be necessary according to athletes’ emotional state. Therefore, it is important to assess and quantify mood states throughout the season in team sports, including among soccer players. The Profile of Mood States (POMS) is a widely used questionnaire that assesses emotional states characterized by positive or negative feelings and can be administered repeatedly to assess changes in mood state. This review aims to assess and summarize the current literature on mood state variation in soccer players with a specific focus on training loads, training modalities, and competitive performance. Methods A literature search was systematically conducted and resulted in 156 records. After removing duplicates, items with irrelevant titles and abstracts were screened out, and full texts were then screened for relevance and compared with inclusion and exclusion criteria. The remaining 37 articles were included in the final qualitative synthesis. Results POMS scores were related to variability in training load, intensity of the training period, modality of training exercises, competitive performance and time of day in soccer players. Common recommendations include monitoring the mood state of soccer players during training sessions, matches, and throughout training periods to detect early signs of psychological disturbance and aid in optimizing high-level training performance. Conclusion The POMS allows for monitoring of players’ psychological state, providing coaches with data to aid in adjusting acute program variables according to players’ psychological states and improve performance. Results offer practical support for the use of a simple POMS measurement as part of an overall program to monitor the players’ psychological states. Results also highlight how training choices (i.e., load and exercise modality) and competitive performance are related to mood states (i.e., tension, anger, confusion, depression, fatigue, and vigor).